2012
DOI: 10.1097/coc.0b013e31820dc075
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Filgrastim, Pegfilgrastim, and Sargramostim as Prophylaxis Against Hospitalization for Neutropenic Complications in Patients With Cancer Receiving Chemotherapy

Abstract: Risk of hospitalization for neutropenic complications during cancer chemotherapy is lower with pegfilgrastim prophylaxis than with filgrastim or sargramostim prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 20 publications
4
52
0
3
Order By: Relevance
“…prolonged neutropenia or fn, efficacy is better with primary prophylaxis than with reactive strategies (that is, secondary prophylaxis) [12][13][14][15][16] . Clinical practice guidelines recommend that g-csf administration should start 24-72 hours after completion of chemotherapy 7 ; however, that timetable is typically the case only for peg administration; fil is often started 5 days afterward 17 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…prolonged neutropenia or fn, efficacy is better with primary prophylaxis than with reactive strategies (that is, secondary prophylaxis) [12][13][14][15][16] . Clinical practice guidelines recommend that g-csf administration should start 24-72 hours after completion of chemotherapy 7 ; however, that timetable is typically the case only for peg administration; fil is often started 5 days afterward 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Being rapidly cleared by the kidneys, fil requires daily subcutaneous injections for approximately 10-14 days after chemotherapy to achieve an absolute neutrophil count exceeding 10×10 3 /μL 17,18 . However, recent observational studies showed an increased risk for fn in patients receiving fil rather than peg, potentially because fil was being administered for a shorter duration than recommended in the guidelines [12][13][14][15][16]17 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se han realizado múltiples modelos de costo-utilidad con el objetivo de comparar lo efectos económicos de diferentes alternativas terapéuticas. Se han reportado estudios aleatorizados con sargramostim, filgrastim y pegfilgrastim, que han mostrado significativamente menos eventos de NF, menos días de estancia hospitalaria relacionados con ésta y, por consiguiente, menores costos relacionados con estos eventos 6 . En otros estudios de farmacoeconomía realizados en EE.UU.…”
Section: Introductionunclassified
“…ha aportado evidencia sólida que indica que el pegfilgrastim no sólo es rentable, sino que también genera ahorro en los costos en las áreas clínicas, reduciendo la media de los costos-día de hospitalización estimados en pacientes que sobrevivieron al evento de NF con respecto a aquéllos que fallecieron. En condiciones basales el pegfilgrastim resulta superior al filgrastim y a otros estimuladores de colonias de granulocitos, con unos costos y efectividad previstos de 4,203 USD y 12,361 días de vida ajustados por calidad (Quality Adjusted Life Days [QALD]) en el caso de ningún factor, de 3,058 USD y 12.967 QALD con pegfilgrastim y de 5,655 USD y 12,698 QALD con el uso de filgrastim, lo que indica que la administración profilác-tica de pegfilgrastim produce beneficios tanto clínicos como económicos [3][4][5][6][7][8][9][10][11][12] . En el Reino Unido, Alemania y Japón se han realizado estudios con estimuladores de colonias de granulocitos en cáncer de mama y se ha estimado que el riesgo absoluto de NF asociada con pegfilgrastim es un 5.5% menor que con 11 días de filgrastim (7 vs. 12.5%) y un 10.5% menor que con 6 días de filgrastim (7 vs. 17.5%).…”
Section: Introductionunclassified